Day Hospital Treatment for Anorexia Nervosa: A 12‐Month Follow‐up Study1. (14th May 2015) - Abbate‐Daga, Giovanni; Marzola, Enrica; De‐Bacco, Carlotta; Buzzichelli, Sara; Brustolin, Annalisa; Campisi, Stefania; Amianto, Federico; Migliaretti, Giuseppe; Fassino, Secondo
Abstract Day hospitals (DHs) represent a treatment option for anorexia nervosa (AN), a mental disorder that is difficult to treat and has no evidence‐based treatments available. We aimed to determine the effectiveness of a DH treatment that was specifically focused on the emotions of severe AN patients. Body mass index and eating psychopathology were the primary outcome measures. Fifty‐six adult patients with AN were assessed upon admission, at the end of treatment (EOT) and at a 12‐month follow‐up evaluation (T18) using Eating Disorders Inventory‐2, Beck Depression Inventory, Hamilton Rating Scale for Anxiety and Brief Social Phobia Scale. All participants received a multidisciplinary treatment programme that focused on psychodynamic psychotherapy. Seventy‐eight per cent of participants reported positive outcomes at EOT and 68% at T18. Moreover, 82.1% and 65.4% of long‐standing patients showed positive outcomes at EOT and T18, respectively. All measures of psychopathology were significantly improved at EOT and were maintained at follow‐up. Our DH was effective at treating severe AN patients; however, further investigations of the processes of change are warranted. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.